Streptococcus thermophilus Attenuates Inflammation in Septic Mice Mediated by Gut Microbiota - Han, Fu; Wu, Gaofeng; Zhang, Yijie; Zheng, Haotian; Han, Shichao; Li, Xiaoqiang; Cai, Weixia; Liu, Jiaqi; Zhang, Wanfu; Zhang, Xiaowei; Hu, Dahai (Frontiers in Microbiology, 2020)
Sepsis is a life-threatening organ dysfunction symptom caused by a dysregulated host response to infection and lack of effective treatment method. Supplementation of probiotic is emerged as a potential biotherapy for inflammatory diseases recent years, but its role in protecting viscera against the damage caused by sepsis and the underlying mechanism is poorly understood. Streptococcus thermophilus 19 is one of the well-studied probiotics, which is selected in this study among seven strains isolated from homemade yogurt since its optimal ability of suppressing the inflammation response in vitro. It showed significant decrease the expression of TNF-α, IL-1β and IL-6 in the co-culture of S. thermophilus 19 and LPS-treated mouse macrophage. The effect of S. thermophilus 19 in mice and the response of mice gut microbiota were investigated subsequently. In LPS-induced septic mouse model, S. thermophilus 19 was highly resistant to LPS and exhibited significantly decreased expressions of inflammatory factors compared to LPS-treated mice. A MiSeq-based 16S rDNA sequence analysis revealed that the decrease of gut microbial diversity in mice intraperitoneally injected with 1 mg/ml LPS were mitigated by the administration of S. thermophilus 19. Fusobacterium significantly decreased during the development of sepsis and raised again after supplement strain 19 and while Flavonifractor showed opposite trend, which demonstrated these two genera were the key bacteria may function in the mice gut microbiota for alleviation of LPS-induced inflammation reaction. To conclude, S. thermophilus 19 may be a potential candidate for novel biotherapeutic interventions product against inflammation caused by sepsis.